Колективний трудовий спір та конфлікт: відмінності понять - Cокол, М.; Sokol, М. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті порівнюються думки вчених щодо поняття трудового спору. Подано визначення спору в широ- кому та вузькому значеннях. Установлено відмінність між словами «спір», «конфлікт» і «розбіжність». У статті наведено порівняльний аналіз між визначеннями трудового спору в українському законодавстві та в законодавстві європейських країн. Управління конфліктом повинне включати діагностику й прогнозування конфлікту; його попередження та профілактику; регулювання й оперативне вирішення.This article compares the views of different scientists on the definition of the category «collective employment dispute». The definition of the dispute is given in the broad and narrow sense of the phenomenon. The difference between the terms «dispute», «conflict» and «disagreement» is set. Disagreement is of the primary link to the dispute, when the contradictions are resolved through negotiation without the intervention of third parties, the dispute is the contradiction between the parties of social and labor law relations, which are solved by the conciliatory bodies and conflict is the possible extent of the dispute, which is characterized by a deterioration of the situation, and often is solved by the strike. In addition, the article also carries out a comparative analysis between the definitions of the labor dispute and conflict in the Ukrainian legislation and the legislation of European countries.
Collective Employment Dispute and Conflict: the Differences of Concepts
Keywords: спір; конфлікт; розбіжність; соціальна конфліктність; управління конфліктами; argument; conflict; discrepancy; social conflict; conflict management